Place identity, autobiographical memory and life path trajectories: The development of a place-time-identity model. (April 2019) - Lengen, Charis; Timm, Christian; Kistemann, Thomas
Abstract: The ability to remember, recognize and reconstruct places is a key component of episodic autobiographical memory. In this respect, place forms an essential basis for the unfolding of experiences in memory and imagination. The autobiographical memory is seen to contribute to a sense of self and place identity. The aim of this study was to concertedly analyze paintings, autobiographical narrations and places of birth and life of clients under treatment at a psychiatric clinic in Switzerland who were manifesting psychiatric disorders, e.g. depression, anxiety disorders, bipolar disorder, personality disorder, substance dependence, and dementia. Each client exhibited distinctive attitudes and approaches towards life characterized by unique personal mental constructs for living in given places of time episodes that worked towards shaping the development of their identities as well as the development of their health. For these clients, place and time function together to leave a mark, a trajectory, that can hinder or help the resolution of a psychiatric condition. Based on six representative cases, we illustrate how each painting, each biographical narration and each interview reveals deeper structures of individual perception, emotions, feelings, coping strategies, and capacities to reflect and identify with place-time trajectories. Based on this analysis, a place-time-identity model has been developed, which emphasizes the importance of narration, the structure of personality, and emotional experiences in the development of the 'relay station' of episodic autobiographical memory, self and autonoetic consciousness: these three elements are not only connected through their embeddedness in time, but also through their embeddedness in place. In this context, place provides an external fundus of memory, capable of supporting humans in healthy recollection and remembering. The process of placing appears to contribute to the creation of self-esteem and identity. This psycho-geographical place-life-time approach is contrasted to phenomenological place-space-time theories of Husserl, Heidegger, Bachelard, and Sloterdijk. Highlights: Episodic autobiographical memory connects through embeddedness in time and place. Memories of place influence the formation of early and subsequent identity. Place and time are parts of the self: 'placelessness' changes the self-concept. Fault lines of personality and socio-cultural aspects determine our life paths. Neuroscience, phenomenology and time geography enable place identity understanding.